The Effect of Two Bonding Agents Generations On Microleakage Of Composite Resin Using Two Light Curing Systems. - Emad F AL-Khalidi; Abdulla MW AL-Shammaa; Nadia H Hasan (University of Mosul, College of Dentistry, 2011)
Aim: To evaluate the effect of two bonding systems and two curing systems on sealing ability of class V composite restorative materials. Materials and methods: This study was performed in vitro on 40 caries free upper first premolar teeth. The Standardized class V cavity preparation on buccal and lin-gual surfaces of each tooth was done. Then the teeth were randomly divided into two major groups each of twenty. 40 cavities were performed on these teeth and the first group7th generation bonding agent (i Bond) were applied according to the manufacturer instructions and single increment of univer-sal composite (XRV Herculite) from kerr were applied and twenty of the cavities were cured with con-ventional light cure device (astralis-5) and the other twenty cavities were cured with a LED. While the second group 5th generation (Excite bonding agent) applied according to the manufacturer instructions. And filled with universal composite (tetric).Twenty of the cavities light cured with conventional light cure device and the other twenty cavities cured with LED light cured device. Then the teeth were stored in normal physiological saline in an incubator at (37Co) half of each sub group (10 cavities) were stored for one day and the second half stored for one week. Then the teeth were thermo cycled for (200) cycles, after thermo cycling all teeth were immersed in a freshly prepared solution of 2% methylene blue for (24) hours at (37Co). Results: The results showed that there was no statistically significant difference between samples cured using conventional light curing system and those cured using LED light curing system. The type of bonding system and composite material used in this study had no sig-nificant effect on reducing microleakage. Samples aged for seven days produced significantly higher levels of microleakage than that for one day. Conclusions: All samples in this study showed microlea-kage with different levels. Microleakage increases as the age increases. Neither the types of light curing system nor the types of bonding were able to reduce microleakage.